Wpływ walorów turystycznych na rozwój społeczno-gospodarczy województwa małopolskiego - Fyda, Agnieszka (My University, 2013)
Głównym celem niniejszej pracy jest pokazanie związku pomiędzy walorami turystycznymi a rozwojem regionalnym w województwie małopolskim oraz wskazanie czynników kształtujących relacje miedzy nimi. Aby zrealizować przedstawiony cel przeprowadzono kwestionariusz ankiety na grupie 70 osób, który miał za zadanie udowodnienie w/w celu. Przeprowadzona analiza daje nam informację, iż walory turystyczne znacznie wpływają na rozwój społeczny i gospodarczy, dając szansę poprawy standardu życia mieszkańców miejscowości turystycznych, rozwoju przedsiębiorczości, powstania nowych miejsc pracy i zmniejszenia bezrobocia czy napływu nowych inwestycji.

The main objective of this work is an indication of the presence of a relationship between tourist bonded and regional development in the Lesser Poland Voivodeship and an indication of the factors shaping the relationships between them. In order to achieve the objective of the survey questionnaire was presented to a group of 70 people, who had to prove in the end. Analysis gives us information that effects tourism appreciably affect the social and economic development by giving a chance to improve the standard of living of the inhabitants of the village tourism, entrepreneurship development, creation of new jobs and reducing unemployment is the influx of new investments.
The impact of tourism values on socio-economic development of Małopolska region
Keywords: turysta; rozwój; walory turystyczne; region; ruch turystyczny; turystyka; tourist; development; tourist assets; region; tourist movements; tourism